2009
DOI: 10.1002/app.30167
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of Bombyx mori silk yarns studied with tensile testing method

Abstract: The mechanical properties of Bombyx mori silk yarns and baves were investigated with tensile testing method. After silk yarns were pre-extended at different strain levels and fixed for a while followed by recovery process, the tensile characteristics were examined in detail. It was commonly observed that low preliminary extensions up to 2-3% do not cause the changes of the mechanical properties and stress-strain curves because they result in small structural changes and distortions, which were recovered within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Meanwhile, the sericin still covers the surface of fibers and plays a protective role, so that the speed of photo-degradation of the inner fibers slows down. 44,45 With only 38℃ water, its influence equals the partial degumming effect, as shown in Figures 8(a)–(f). Comparing the breaking strength of silk fibers for UV irradiation and water ageing, we notice that the speed of water and light ageing is faster.…”
Section: Resultsmentioning
confidence: 88%
“…Meanwhile, the sericin still covers the surface of fibers and plays a protective role, so that the speed of photo-degradation of the inner fibers slows down. 44,45 With only 38℃ water, its influence equals the partial degumming effect, as shown in Figures 8(a)–(f). Comparing the breaking strength of silk fibers for UV irradiation and water ageing, we notice that the speed of water and light ageing is faster.…”
Section: Resultsmentioning
confidence: 88%
“…For example, shear-induced self-assembly of native silk fibroin into fibril was reported by atomic force microscopy. , He et al reported that the N-terminal domain of B. mori silk fibroin functions as a pH-responsive self-assembly module that could prevent β-sheet formation at neutral pH yet could initiate fibroin assembly as pH decreases . The pH-induced change in the rheological properties of B. mori silk fibroin was also examined. The promotion of random coil to β-sheet structures has been induced by several ions such as K + or Ca 2+ . ,, The important role of water molecules during silk fiber formation was also discussed in detail. ,,,, Thus, NMR provides a great contribution to clarify these interactions during the formation of strong and tough fibers from aqueous solution. , The structural change of B. mori silk fibroin fiber by stretching has been intensively studied and the change in the noncrystalline region has been emphasized. , Thus, domain-specific information on the crystalline and noncrystalline domains is likely to be important in understanding the structural change during the fiber formation process and the origin of the strong and tough fibers in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Materials and UV-irradiation process Uncoated B. mori silk fibers Silkworm (B. mori) silk cocoons purchased from Koza Han in Bursa, Turkey were opened and degummed with the method described earlier [23]. Because the degummed silk fibers were obtained in the form of bave consisting of the two constituent brins of the cocoon fiber which could not be separated.…”
Section: Methodsmentioning
confidence: 99%